Articulation of geminate obstruents in the Ikema dialect of Miyako Ryukyuan: A real-time MRI analysis. (29th April 2023) - Fujimoto, Masako; Shinohara, Shigeko; Mochihashi, Daichi
Abstract : The Ikema dialect of Miyako Island in Okinawa, Japan, has typologically rare word-initial and voiced geminate obstruents (e.g. /vva/ 'you', /ffa/ 'child', /tta/ 'tongue', /badda/ 'side'). These sounds are marked in two ways: Voicing through geminate obstruents is hard to produce and initial voiceless plosives seem to be difficult to perceive. This study investigated real-time magnetic resonance imaging (rt-MRI) to examine the articulatory settings underlying contrasts between singleton and geminate obstruents. Our analyses of two male speakers' utterances showed the following five characteristics: (i) geminate obstruents in Ikema have longer duration of articulatory constrictions regardless of position and consonant types; (ii) the voiced alveolar plosive geminate /dd/ is articulated with a larger linguopalatal contact than its singleton counterpart but such difference depends on the speaker for the voiceless plosive pair /tt/–/t/ and the fricative pairs /ss/–/s/ and /zz/–/z/; (iii) alveolar voiceless plosives /t/ and /tt/ have a greater degree of linguopalatal contact than their voiced counterparts /d/ and /dd/, respectively, but fricatives show inter-speaker variation; (iv) fricatives do not show any systematic difference in degree of (midsagittal) linguopalatal contact between geminates and singletons, or between voiceless and voiced consonants; and (v) voiced geminate obstruents are accompanied by pharyngeal expansion for both speakers and by lowering the larynx for one speaker, and never by lowering of the velum. We also observed that voiced fricatives tend to realize as affricates, which we interpret as part of the articulatory adjustments for (full) voicing of phonologically voiced geminate fricatives.